PENGARUH KEMASAN DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN - Ayu Partiwi; Eti Arini (Yayasan Insani Mandiri Santani, 2021)
The purpose of this study is to determine the effect of Packaging and Brand Image on purchasing decision on consumer of Cita Rasa Store in Soevenir Center of Bengkulu city and to find out which factors having the more dominant effect on the purchasing decision. The researcher used the questionnaire method to 110 respodents. The Population used were lempuk durian consumer of Cita Rasa store in souvenir center city of Bengkulu city. The sampling was the accindental sampling technique. Based on the results of multiple linear regression, the form of regression equation is Y = 2.955 + 1.200 ( ) + 0.345 ( ). The results of the research and the hypothesis show that the Packaging shows the value of > (9.732 > 1.982) and (sig = 0,000 < 0,050), while Brand Image shows the value of tcount > (3.146 > 1.982) and (sig = 0,000 < 0,050). Simultaneously Packaging and Brand Image have a significant effect on purchasing decision. Partially the two variables Packaging and Brand Image have a significant effect on purchasing decision. It is better if the producers can continue to maintain and even improve their products so that the main objectives of marketing can be achieved.Keywords: Packaging, Brand Image, Buying Decission